2021
DOI: 10.3390/app11020856
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Powered Membrane Technology: Electrical Energy Storage Options for a Photovoltaic-Powered Brackish Water Desalination System

Abstract: The potential for lithium-ion (Li-ion) batteries and supercapacitors (SCs) to overcome long-term (one day) and short-term (a few minutes) solar irradiance fluctuations with high-temporal-resolution (one s) on a photovoltaic-powered reverse osmosis membrane (PV-membrane) system was investigated. Experiments were conducted using synthetic brackish water (5-g/L sodium chloride) with varied battery capacities (100, 70, 50, 40, 30 and 20 Ah) to evaluate the effect of decreasing the energy storage capacities. A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Storing energy in hydrogen is another option, but the conversion efficiency must be improved at both ends. For short-term fluctuations, flywheels [41], supercapacitors [42] or compressed air storage [43] is options to develop. In the case of already-dispatchable CSP, the development of more efficient Brayton cycles that operate with air or supercritical CO 2 is proposed [44].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Storing energy in hydrogen is another option, but the conversion efficiency must be improved at both ends. For short-term fluctuations, flywheels [41], supercapacitors [42] or compressed air storage [43] is options to develop. In the case of already-dispatchable CSP, the development of more efficient Brayton cycles that operate with air or supercritical CO 2 is proposed [44].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…However, one of the main challenges of a solar-driven system is related to energy storage capacities. The prospective for lithium-ion (Li-ion) batteries and supercapacitors (SCs) on a photo voltaic-powered RO membrane (PV-membrane) system was evaluated, and it was observed that average specific energy consumption (SEC) of 4 kWh/m 3 with fully charged batteries is used to produce clean water [178].…”
Section: Development Of Renewable Energy-driven Membrane Systemmentioning
confidence: 99%